Writing and editing for digital media - Carroll, Brian, 1965- (Routledge, 2018)
Teaches students how to write effectively for online audiences - whether they are crafting a story for the online face of a daily newspaper or a personal blog. This book focuses on writing primarily for journalism, public relations, and marketing and advertising audiences.